Chronos in Aristotle's Physics: On the Nature of Time - Harry, Chelsea C. (SpringerBriefs in philosophy, 2015)
Keywords: Aristotle. Physics; Time; Philosophy; Philosophy of nature; Philosophy; Physics; dept.phi; faculty_collection

Heidegger in France - Janicaud, Dominique (Studies in Continental thought, 2015)
Dominique Janicaud claimed that every French intellectual movement--from existentialism to psychoanalysis--was influenced by Martin Heidegger. This translation of Janicaud's landmark work, Heidegger en France, details Heidegger's reception in philosophy and other humanistic and social science disciplines. Interviews with key French thinkers such as Françoise Dastur, Jacques Derrida, Éliane Escoubas, Jean Greisch, Philippe Lacoue-Labarthe, Jean-Luc Marion, and Jean-Luc Nancy are included and provide further reflection on Heidegger's relationship to French philosophy. An intellectual undertaking of authoritative scope, this work furnishes a thorough history of the French reception of Heidegger's thought.--Publisher website.
Keywords: 20th century; Philosophers; France; Heidegger, Martin, 1889-1976; Philosophy, French; Interviews; dept.phi; faculty_collection

Fragments of a Lost Homeland: Remembering Armenia - Marsoobian, Armen (I.B. Tauris & Co. Ltd., 2015)
Keywords: 1801-1900; Dildilian family; Armenian Genocide, 1915-1923; History; Personal narratives, Armenian; Armenian Genocide, 1915-1923; Armenia; SCSU Faculty Scholar Award; award_winner; dept.phi; faculty_collection

Roman Catholic monasticism in Poland: A brief overview of selected issues - Górniak-Kocikowska, K. (Monasticism in Eastern Europe and the Former Soviet Republics, 2015)
Keywords: dept.phi

In defense of the critical philosophy: On Schelling's departure from Kant and Fichte in Abhandlungen zur Erläuterung des Idealismus der Wissenschaftslehre (1796/1797) - Harry, C.C. (Journal of Speculative Philosophy, 2015)
This article considers the second treatise of Schelling's Abhandlungen zur Erläuterung des Idealismus der Wissenschaftslehre (Treatises Explaining the Idealism of the Science of Knowledge, 1796/97), a lesser-known work from the early Schelling. Here, Schelling proposes to defend the critical position insofar as it purports to be a system based on human reason, but instead he issues a backhanded critique of the assumption on behalf of the critical philosophers to try and limit the bounds of pure reason by means of their own use of reason. Schelling then offers an alternative way to think about the relationship of mind (Geist) and matter in nature. This article argues that Schelling's actual explanation of the critical philosophy as a position founded by reasonable minds ultimately belies his promise to defend it, thus calling into question that Schelling's thought prior to 1800 was a mere reiteration of Kantian/Fichtean transcendentalism. Copyright © 2015 The Pennsylvania State University, University Park, PA.
Keywords: Critical philosophy; Fichte; Kant; Naturphilosophie; Shelling; dept.phi

On the fundamental dissimilarity of aristotelian and Kantian time concepts - Harry, C.C. (Idealistic Studies, 2015)
In Aristotle's Physics iv 10-14, Aristotle argues for a time concept derived with, on a weak version, sense perception, and, on a strong version, from sense perception along with intellection (nous), from change in nature. On both accounts, actualized time for Aristotle requires cognitive faculties. Aristotle's time concept has thus been linked with Kant's treatment of time in the Transcendental Aesthetic of his First Critique. More importantly, the conclusion that time is "unreal" for Aristotle elicits charges of adulterating Aristotle's conclusions by reading Aristotle's Physics with a Kantian lens. In this paper, I examine the context of Kant's conclusions about time and, by way of a contrast between the Aristotelian and Kantian projects, argue for a fundamental dissimilarity of their accounts. And yet, I reserve the possibility that one both ascent to this fundamental dissimilarity and hold that Aristotle was not a temporal realist. © 2015. Idealistic Studies.
Keywords: dept.phi; peer-reviewed

Taking Time - Harry, C.C. (SpringerBrief. Philos., 2015)
Despite the language we saw in the previous chapter, which allowed for time apprehension by perception and marking, in Physics iv 14, Aristotle famously argues that time is dependent on nous. © 2015, The Author(s).
Keywords: Human Child; Nonhuman Animal; Pure Actuality; Sense Perception; Time Perception; dept.phi

The Armenian Genocide of 1915: Armen T. Marsoobian explores the complex history of one of the 20th-century's worst and most neglected crimes against humanity - Marsoobian, A.T. (History Today, 2015)
Keywords: dept.phi; ⛔ No DOI found

Computer ethics beyond mere compliance - Volkman, Richard (Journal of Information, Communication and Ethics in Society, 2015)
Purpose – The paper aims to examine the nature of computer ethics as a field of study in light of 20 years of Ethicomp, arguing that computer ethics beyond mere compliance will have to be pluralistic and sensitive to the starting places of various audiences. Design/methodology/approach – The essay offers a philosophical rather than empirical analysis, but the ideal of open inquiry is observed to be manifest in the practice of Ethicomp. Findings – If computer ethics is to constitute a real engagement with industry and society that cultivates a genuine sensitivity to ethical concerns in the creation, development and implementation of technologies, a genuine sensitivity that stands in marked contrast to ethics as “mere compliance”, then computer ethics will have to persist in issuing an open invitation to inquiry. Originality/value – The celebration of 20 years of Ethicomp is an occasion to reflect on who we are and what we mean to be doing. Inclusive of previous accounts (e.g. Moor and Gotterbarn), while going beyond them, an inquiry-based conception of computer ethics makes room for all the various dimensions of computer ethics. ©Emerald Group Publishing Limited
Keywords: Collaboration; Community evolution; Computer ethics; Information ethics; Philosophy; Teaching innovations; dept.phi; peer-reviewed

Physics iv 10-11 as a Parallel Account - Harry, Chelsea C. (Chronos in Aristotle’s Physics: On the Nature of Time, 2015)
Given the context of the Physics just explored, it will not be a surprise if time (chrόnos) in Aristotle’s analytic of time turns out to be not a being qua itself but an attribute of motion, an interval.
Keywords: Infinite Divisibility; Infinite Time; Internal Inconsistency; Natural Object; Underlying Unity; dept.phi

Time in Context - Harry, Chelsea C. (Chronos in Aristotle’s Physics: On the Nature of Time, 2015)
The key to taking in Aristotle’s treatise on time is to approach it with the understanding that Aristotle was not a philosopher concerned with time —in questions about time or in delimiting the being of time.
Keywords: Accidental Change; Accidental Form; Natural Object; Predicative Change; Privative Form; dept.phi